2022
DOI: 10.1038/s41598-022-17443-1
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of skin ageing genes: gene pleiotropy and genes on the chromosomal band 16q24.3 may drive skin ageing

Abstract: Skin ageing is the result of intrinsic genetic and extrinsic lifestyle factors. However, there is no consensus on skin ageing phenotypes and ways to quantify them. In this systematic review, we first carefully identified 56 skin ageing phenotypes from multiple literature sources and sought the best photo-numeric grading scales to evaluate them. Next, we conducted a systematic review on all 44 Genome-wide Association Studies (GWAS) on skin ageing published to date and identified genetic risk factors (2349 SNPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…In our recent systematic review of skin ageing, 10 we found that the quantification of skin ageing phenotypes in the field can be broadly classified into two categories: quantification using a written descriptive scale and quantification using a photo‐numeric scale.…”
Section: Discussionmentioning
confidence: 99%
“…In our recent systematic review of skin ageing, 10 we found that the quantification of skin ageing phenotypes in the field can be broadly classified into two categories: quantification using a written descriptive scale and quantification using a photo‐numeric scale.…”
Section: Discussionmentioning
confidence: 99%
“…Recently performed genome-wide association studies (GWASs) and other original research works laid the groundwork for a personalized approach to healthcare, where a niche for more effective skincare approaches certainly exists [20][21][22]. In the literature, there are different types of investigations with different objectives, where some of them are orientated to a thorough pathophysiological and genetical analysis [3,22], while others are focused on a more practical approach, trying to find the best way to utilize scientific findings for clinical use [6,10,11]. Our work stands out from both categories by combining routine laboratory investigations with molecular genotyping results offering regular blood tests that would depend on individual skinassociated genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Ng & Chew (2022) [3] performed a systematic review of 44 GWAS studies on skin aging and identified 19…”
Section: Genome-wide Association Studies (Gwas) and Principalmentioning
confidence: 99%
“…Skin aging compared to other organs is a complex process influenced by two main factors: intrinsic, or genetic; and extrinsic, or environmental [1,2] . Since skin aging suffers from both genetic and environmental influences, the study of these variables is extremely important for precision medicine, in which treatments can be customized according to individual needs [3,4] .…”
Section: Introductionmentioning
confidence: 99%